Realizing rights : transforming approaches to sexual and reproductive well-being - Cornwall, Andrea, 1963-; Welbourn, Alice (Zed Books ; Distributed in the USA exclusively by Palgrave, 2002)
This book offers a wide range of innovative examples from around the world related to fundamental shifts in thinking and the practice of reproductive rights. From popular theater in Nigeria to participatory research in Britain, from role-playing in Cambodia to visualizing reproductive health in Zimbabwe, and from collaborative planning in Egypt to community dialogue in the Andes, these twenty-four chapters reveal the value of transforming approaches to sexual and reproductive wellbeing. All begin with the need to engage women, men, and youth more directly in determining pathways to change, and all highlight both the complexities and the possibilities of making rights real. Contributers: Cheryl Overs, Jo Doezema & Meena Shivdas - Kathryn Faulkner & Jessica Knott - Helen Lynn & Diana Ward - Rayah Feldman, Joanne Manchester & Caroline Maposhere - Oga Steve Abah - Ann Sutherland & Felicia Sakala - Alice Welbourn - Jerker Edstrom, Arturo Cristobal, Tilly Sellers & Chulani De Soyza - Matthew Shaw - Ann Smith & John Howson - Lucy Antivelink, Andrew Abalio, Doreen Byateesa, Naome Gonahasa, Margaret Kabanda, Connie Kajura, Bernard Lukwago, John Mike, Mary Mwiri, Lucy Shillingi, Peter Ssebbanja, Stephen Watuwa, with John Mwesigwa, Ben Osuga, Ros Cooper & Alice Welbourn - Tilly Sellers, Pok Panhavichetr & Ly Chansophal - Maria De Nazareth & Agra Hassen - Barbara Kaim - Zane Ibrahim - Karla Galvao Adriao, Benedito Medrado, Jorge Lyra & Pedro Nascimento - Jill Lewis - Andrea Cornwall - Renu Khanna, Korrie De Koning, Sneha Khandekar, Anagha Pradhan Swati Pongurlekar, & Usha Ubale - Pitamber Dhungana, Krishna Prasai, Tara Gynawali, Badri Pant, Kate Butcher - Lisa Howard-Grabman, Cynthia P. Willis, Elizabeth Arteaga, Carla Queierolo And Ccolla, & Sejas Perez - Martin Westerby & Janet Harris - Frances Mcconville - Carla Rull Boussen & The Salammbo Group